2y - 3/4x = -10

y+1/4x=0

Solve one of the equations for x:

y + 1/4x = 0

(I'm going to multiply the entire equation by 4 to get rid of the fraction):

4(y+1/4x = 0)

4y + x = 0

x = -4y

Now substitute x = -4y into the first equation:

2y - 3/4(4y) = -10

2y - 3y = -10

-y = -10

y = 10

Substitute y = 10 into the first equation. Again, I'm going to use the equation multiplied by 4 because it's easier:

4(10) + x = 0

40 + x = 0

x = -40

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up